PENDIDIKAN BERBASIS BUDI PEKERTI Menguak Karakter Pendidikan Bangsa yang Terlupakan - Zuhairansyah Arifin (Lembaga penelitian dan pengabdian kepada masyrakat, 2014)
Moral or character education represents one of the principal loads in the implementation of the Competency-Based Curriculum and it is carried out by means of an integrated learning approach. Problems arise because not all teachers possess the potential sensitivity adequate for identifying and analyzing materials for character education in the learning materials or lesson books used. The teachers tend to merely teach whatever is explicit in the learning materials while the materials for character education implicit in the learning materials are not perceived and revealed. As a result, the character education implied is not worked out and does not reach the learner. To solve the problem, certain strategies need to be employed in carrying out character education integrated in the competency-based class subjects. The strategies cover presentation and learning strategies, the former further covering implicit and explicit strategies and the latter further covering deductive and inductive strategies. The identification, interpretation, and analysis of materials for character education should be made to fit the local cultural context (implying Contextual Teaching and Learning).